FAKTOR YANG BERPENGARUH TERHADAP STRESS KERJA PADA PEKERJA AIR TRAFFIC CONTROLLER - Aliyatur Rofi’a; Umi Rahayu; Suprijandani . (Poltekkes Kemenkes Surabaya, 2019)
Air Traffic Controller is a job that plays an important role in air traffic in charge of controlling aircraft activity. So, it is required to always be ready and not to make the slightest mistake given the impact of air traffic accidents. The complexity and responsibility on the physical health of workers and the chaos of air traffic and aircraft accidents that can endanger the lives of other individuals. The purpose of this study was determine the factors that influence work stress on Air Traffic Controller workers at Juanda International Airport in 2019.This type of research is analytic observational research with a cross-sectional study design. The procedure of data collection is done by observation, interviewing, disseminating and filling out the related questionnaire, and testing the work environment. The sample in this study were 60 Air Traffic Controller workers by simple random sampling. Data were analyzed by univariate, bivariate, and multivariate with statistical test namely Logistic Regression.The results of work stress assessment showed that the work stress level of most workers experienced a mild work stress of 55%, workers who experienced moderate work stress as much as 45%, while workers who experienced severe work stress and workers who did not experience work stress did not exist. Factors that influence the work stress on Air Traffic Controller workers at Perum LPPNPI Madya Surabaya Branch Juanda International Airport in 2019 are workload, education, and work routine.It is recommended to measure lighting, temperature, and humidity regularly in the workspace, scheduling work hours for sure, checking work stress, adjusting to work, and maximizing rest time. Keywords : Air Traffic Controller, Workload, Work Stress